2012
DOI: 10.1038/bjc.2012.448
|View full text |Cite
|
Sign up to set email alerts
|

Risk and prognostic significance of metachronous contralateral testicular germ cell tumours

Abstract: Background:Testicular germ cell tumour (TGCT) patients are at increased risk of developing a contralateral testicular germ cell tumour (CTGCT). It is unclear whether TGCT treatment affects CTGCT risk.Methods:The risk of developing a metachronous CTGCT (a CTGCT diagnosed ⩾6 months after a primary TGCT) and its impact on patient's prognosis was assessed in a nationwide cohort comprising 3749 TGCT patients treated in the Netherlands during 1965–1995. Standardised incidence ratios (SIRs), comparing CTGCT incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
4
29
0
Order By: Relevance
“…Hartmann's et al analysis covers the period between 1975 and 1996 when CTH was not standard treatment method for patients with mediastinal germ cell tumors. Patients with testicular cancers treated with CTH were found to have lower risk of developing metachronous testicular cancer than those treated without CTH (20,21). Therefore, the application of CTH in patients with extragonadal germ cell tumors might have a similar influence on risk of developing testicular cancers during follow-up but this hypothesis must be further verified in the future.…”
Section: Discussionmentioning
confidence: 97%
“…Hartmann's et al analysis covers the period between 1975 and 1996 when CTH was not standard treatment method for patients with mediastinal germ cell tumors. Patients with testicular cancers treated with CTH were found to have lower risk of developing metachronous testicular cancer than those treated without CTH (20,21). Therefore, the application of CTH in patients with extragonadal germ cell tumors might have a similar influence on risk of developing testicular cancers during follow-up but this hypothesis must be further verified in the future.…”
Section: Discussionmentioning
confidence: 97%
“…One potential advantage of carboplatin discussed in the MRC/EORTC study has been that of a lower risk of primary germ cell tumours in the contralateral testis with adjuvant carboplatin as opposed to RT. Although the results are promising, longer follow‐up has shown that the contralateral risk is not completely eliminated and the possibility that later occurrences of contralateral primary tumour may be seen with longer follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…5 The unusual feature of the patient reported here is the development of a third primary tumour. Of the 403 case reports indexed in MEDLINE under both the MeSH headings "testicular neoplasm" and "neoplasms, multiple primaries," none in the last 25 years included patients with 3 or more metachronous primary testicular neoplasms.…”
Section: Discussionmentioning
confidence: 92%